1983
DOI: 10.1016/0090-8258(83)90166-x
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapeutic alternatives to standard management of adenocarcinoma of the endometrium

Abstract: Primary radiotherapy as an alternative management for adenocarcinoma of the endometrium was chosen for 117 patients treated at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1987
1987
1999
1999

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Despite this recommendation none of these authors reported a better disease specific survival in patients who were treated with additional external radiotherapy. More recently numerous authors have suggested that external radiation therapy does not contribute to survival and increase complications (11,17). It is pointed out that our good results are achieved with intracavitary brachytherapy alone.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Despite this recommendation none of these authors reported a better disease specific survival in patients who were treated with additional external radiotherapy. More recently numerous authors have suggested that external radiation therapy does not contribute to survival and increase complications (11,17). It is pointed out that our good results are achieved with intracavitary brachytherapy alone.…”
Section: Discussionmentioning
confidence: 79%
“…Radiation therapy has proved effective in the treatment of medically inoperable endometrial carcinoma (10). A 5-year overall survival is quoted to be 41-73% for radiation therapy alone (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) and 80-94% for surgery (23). Disease specific survival has been reported to be 64-88% (3,10,15,17,20,24).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have reported that a combination of external radiation therapy followed by intracavitary application has the greatest survival for endometrial carcinoma (13,21,23,26). More recently numerous authors have suggested that external radiation therapy does not contribute to survival and increase complications (11,17). Despite this recommendation none of these authors reported a better disease specific survival in patients who were treated with additional external radiotherapy.…”
Section: Discussionmentioning
confidence: 99%